Prediabetes is associated with loss of appendicular skeletal muscle mass and sarcopenia - Li, Shuying; Mao, Jiangfeng; Zhou, Weihong (Frontiers in Nutrition, 2023)
Background Decreasing mass and metabolism in skeletal muscle are associated with increasing insulin resistance (IR) and type 2 diabetes mellitus (T2DM). The causal relation between sarcopenia and abnormal glucose metabolism may be bidirectional. This investigation is aimed to explore the detailed correlation between prediabetes and sarcopenia in United States (US) adults. Methods A total of 22482 adults aged ≥ 20 years in the National Health and Nutrition Examination Survey (NHANES) were included. Generalized linear models were conducted to examine associations between diabetes status, serum glucose, glycohemoglobin (HbA1c), and sarcopenia. Generalized additive models and smooth fitting curves were used to examine the non-linear relationship between HbA1c and ASMBMI. Sarcopenia was defined as ASMBMI (appendicular skeletal muscle mass/body mass index) < 0.789 for males, and < 0.512 for females based on the cut-off values of the Foundation for the National Institutes of Health (FNIH)Sarcopenia Project. Results After fully adjusting for multiple covariates, sarcopenia was directly correlated with prediabetes [OR (95%CI) = 1.230(1.057, 1.431), p= 0.008] and T2DM [OR (95%CI) = 2.106(1.625, 2.729), p <0.001]. In non-T2DM population, HbA1c was negatively correlated with ASMBMI [β (95%CI) = -0.009 (-0.013, -0.005), p <0.001]. The correlations only persisted in males. Furthermore, in male non-T2DM population, the association of HbA1c and ASMBMI presents an inverted U-shape curve with an inflection point of HbA1c 5.2%. Conclusion Prediabetes is associated with increased risk of sarcopenia. HbA1c is an independent risk factor for loss of appendicular skeletal muscle mass and sarcopenia when HbA1c greater than 5.2% in the male non-T2DM population.